Variation in electronic test results management and its implications for patient safety: A multisite investigation. (27th July 2020) - Thomas, Judith; Dahm, Maria R; Li, Julie; Smith, Peter; Irvine, Jacqui; Westbrook, Johanna I; Georgiou, Andrew
Abstract: Objective: The management and follow-up of diagnostic test results is a major patient safety concern. The aim of this qualitative study was to explore how clinicians manage test results on an everyday basis (work-as-done) in a health information technology–enabled emergency department setting. The objectives were to identify (1) variations in work-as-done in test results management and (2) the strategies clinicians use to ensure optimal management of diagnostic test results. Materials and Methods: Qualitative interviews (n = 26) and field observations were conducted across 3 Australian emergency departments. Interview data coded for results management (ie, tracking, acknowledgment, and follow-up), and artifacts, were reviewed to identify variations in descriptions of work-as-done. Thematic analysis was performed to identify common themes. Results: Despite using the same test result management application, there were variations in how the system was used. We identified 5 themes relating to electronic test results management: (1) tracking test results, (2) use and understanding of system functionality, (3) visibility of result actions and acknowledgment, (4) results inbox use, and (5) challenges associated with the absence of an inbox for results notifications for advanced practice nurses. Discussion: Our findings highlight that variations in work-as-done can function to overcome perceived impediments to managing test results in a HIT-enabled environment and thus identify potential risks in the process. By illuminating work-as-done, we identified strategies clinicians use to enhance test result management including paper-based manual processes, cognitive reminders, and adaptive use of electronic medical record functionality. Conclusions: Test results tracking and follow-up is a priority area in need of health information technology development and training to improve team-based collaboration/communication of results follow-up and diagnostic safety.